A history of British birds / by the Rev. F. O. Morris. - Morris, F. O. (Francis Orpen), 1810-1893. (Tufts University. Tisch Library., 2014)
Vols. 1-3, 5, 7-8 have title on spine: Morris's British birds.; Vol.5